Pendampingan Transformasi Digital Menggunakan Strategi Pemasaran Modern Dalam Meningkatkan Visibilitas Dan Penjualan Produk KWT Puspa Gemari - Permana, Dani; Hoerunisa, Hana; D, Alya Febri Surya; Apriliani, Inge; Rosa, Florensa Marchilaz Della; Rambe, Hasnah; Trisriantama, Muhammad Defan; Salsabila, Alya Dwi (Indonesian Journal Publisher, 2025)
This study aims to implement digital transformation using modern marketing strategies to enhance the visibility and sales of products from the Women Farmers Group (KWT) Puspa Gemari. The research method used is Action Research, involving socialization and training to improve the digital skills of KWT Puspa Gemari members. The work program includes product photography training, social media management, and packaging rebranding to create a more attractive and professional product image. The analysis of the success of this program is measured by data on the effectiveness of the use of digital advertising, website use, WhatsApp business, and also content management on KWT Puspa Gemari social media has a significant role in increasing sales of KWT Puspa Gemari products. With this strategy, KWT Puspa Gemari strengthened their position in the market and became a relevant example of digital transformation for other women farmers' groups.